PENGARUH KOMBINASI PUPUK MAJEMUK NPK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI (Capsicum annum L.) - solihin, Eso; Sudirja, Rija; Maulana, Haris; Kamaluddin, Nadia Nuraniya (Program Studi Agroteknologi Faperta UNIBBA, 2024)
Modern agriculture faces major challenges in achieving sustainable food security and efficient use of resources. One approach that has been adopted is the use of compound fertilizers, which combine several nutrients in one product. This study aims to determine the effect of applying a combination of doses of NPK compound fertilizer (16-16-16) and Liquid Inorganic and determine the best dose combination on the growth and yield of Chili (Capsicum annum L.). This research was conducted in Palasari Village, Cibiru Subdistrict, Bandung City, West Java Province, at an altitude of 725 meters above sea level. The research was conducted from February to May 2022. The method in this study used a Randomized Group Design (RAK), with nine treatments and three replications. Treatments (A) Control, (B) Standard fertilizer (Urea, SP-36, and KCl), (C) 1 NPK + ¼ Liquid Inorganic, (D) 1 NPK + ½ Liquid Inorganic, (E) 1 NPK + ¾ Liquid Inorganic, (F) 1 NPK + 1 Liquid Inorganic, (G) 1 NPK + 1 ¼ Liquid Inorganic, (H) 1 NPK + 1 ½ Liquid Inorganic, (I) 1 NPK + 2 Liquid Inorganic. The results showed that the combination of NPK compound fertilizer treatment F (250 kg/ha NPK 16-16-16 and 1 liter/ha Liquid Inorganic) gave the best results on plant height, plant diameter, number of leaves, number of fruits per plant, fruit weight per plant, fruit length, fruit diameter, fruit weight per plot and fruit weight per hectare.